Administrative barriers, capacity constraints and solutions for the inclusion of agricultural workers in social insurance schemes in the Middle East and North Africa - Nourjelha Mohamed; Lucas Sato (International Policy Centre for Inclusive Growth (IPC-IG), 2022)
The third and final Research Report in the series "Expanding Social insurance for agricultural workers in Middle East and North Africa (MENA): identifying key constraints and discussing policy options" focuses on understanding the administrative barriers and capacity constraints that may hinder the coverage of agricultural workers in social insurance schemes, and which strategies could be considered to address them.
Keywords: 330; social insurance; agricultural workers; capacity constraints; MENA